Tryptophan metabolism and gut flora profile in different soybean protein induced enteritis of pearl gentian groupers - Zhang, Wei; Pang, Aobo; Tan, Beiping; Xin, Yu; Liu, Yu; Xie, Ruitao; Zhang, Haitao; Yang, Qihui; Deng, Junming; Chi, Shuyan (Frontiers in Nutrition, 2022)
The substitution of high-level soy meals for fish meal (FM) generally leads to fish enteritis, accompanied by significant variations in gut flora. Relevant studies have pointed out a close relationship between tryptophan metabolism mediated by gut flora and vertebrate inflammatory bowel disease. Present study examines the role of tryptophan metabolism and gut flora profile in fish enteritis caused by different soybean meals. The 960 groupers were randomly assigned into 4 groups (n = 4), which including: 1) FM (the control group, fed with 50% FM feed), 2) SBM40 (replacing 40% FM with soybean meal), 3) SPC40 (replacing 40% FM with soybean protein concentrate), and 4) FSBM40 (replacing 40% FM with fermented soybean meal). Under average temperature and natural light, the groupers were cultivated with feeds of iso-nitrogen and iso-lipid for 10 weeks. The results showed that soybean meal feeds at all experimental levels had negative effects on fish gut physiology and growth performance. Typical enteritis features and fluctuations of immune system occur, which can be observed in the enzyme activities of total superoxide dismutase and lysozyme and in the contents of immunoglobulin M, complement 3 and complement 4. 16SrDNA high-throughput sequencing indicated that it greatly influenced the gut flora with the abundance of maleficent bacteria, like Vibrio, amplified with increasing dietary soybean meals. According to the “3+2” full-length transcriptome sequencing, soy meals at the three experimental levels inhibited the key gene expressions of tryptophan metabolic pathway in fish gut, however, there are some differences in the types of key genes that are inhibited. The canonical correlation analysis showed that the changes in key gene expressions in tryptophan metabolic pathway had a positive correlation with the expressions of pro-inflammatory genes and negatively correlated with the expression of anti-inflammatory genes. It is speculated from this study that tryptophan metabolism is closely related to fish soy meal-related enteritis, and the abnormal tryptophan metabolism caused by intestinal flora imbalance may play an important role. In the future research, we can further study the tolerance of fish to soy meals feed from two aspects of tryptophan metabolism and intestinal flora changes.